5% Dextrose Nasal Irrigation for Cervical Dystonia: A Case Report - Rabago, David; Suer, Michael (Archives of Clinical and Medical Case Reports, 2021)
Background: Cervical dystonia, the most common form of dystonia, is a painful and disabling movement disorder primarily of idiopathic etiology. While there is no cure, several modalities have been utilized for symptom management including medications, injections, and deep brain stimulation. Case Report: The patient is a now 75-year-old female with a history of painful cervical dystonia. Despite several other treatment modalities including physical therapy, oral medications, and onabotulinum toxin injections, her symptoms continued to worsen. She underwent serial low volume dextrose intra-nasal irrigation and experienced decreased pain and improved cervical range of motion. She performed dextrose nasal irrigation at regular intervals with sustained improvement in her range of motion until treatment was discontinued. Conclusion: This is the first reported case presentation utilizing intranasal irrigation of dextrose solution for the treatment of cervical dystonia. Intranasal dextrose solution appears to be associated with temporary decrease of pain and improved range of motion in this patient with cervical dystonia. LEVEL OF EVIDENCE: V.